2016
DOI: 10.3390/s16111902
|View full text |Cite
|
Sign up to set email alerts
|

Tunnel Magnetoresistance Sensors with Magnetostrictive Electrodes: Strain Sensors

Abstract: Magnetostrictive tunnel magnetoresistance (TMR) sensors pose a bright perspective in micro- and nano-scale strain sensing technology. The behavior of TMR sensors under mechanical stress as well as their sensitivity to the applied stress depends on the magnetization configuration of magnetic tunnel junctions (MTJ)s with respect to the stress axis. Here, we propose a configuration resulting in an inverse effect on the tunnel resistance by tensile and compressive stresses. Numerical simulations, based on a modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…The TER is much enhanced and reaches about 200% at RT with the second polarization method. This study gives 27 a strong argument that the decreasing of TER for the temperature range higher than 120K is mainly due to the thermal fluctuation on the ferroelectric domains.…”
Section: S5 Temperature Dependence Of Transport Behavior With Two Pomentioning
confidence: 71%
“…The TER is much enhanced and reaches about 200% at RT with the second polarization method. This study gives 27 a strong argument that the decreasing of TER for the temperature range higher than 120K is mainly due to the thermal fluctuation on the ferroelectric domains.…”
Section: S5 Temperature Dependence Of Transport Behavior With Two Pomentioning
confidence: 71%
“…Some studies [53,54,55] have shown that pre-magnetized magnetic fields have an effect on the Villari effect of magnetostrictive materials, so we speculated that it also has an effect on the performance of Fe-Ga harvester. We adopt a permanent magnet to provide a pre-magnetized field to the Fe-Ga layer and select three different pre-magnetized positions and layouts to carry out this experiment.…”
Section: Comprehensive Analysis Of Energy Harvesting Characteristicsmentioning
confidence: 94%
“…The system includes an MMS, an inertial sensor, a global positioning system receiver, a vision component, and a navigation algorithm to stabilize and control the flight of an unmanned aerial vehicle. A tunnel magnetoresistance MMS, designed by Tavassolizadeh [6], has been applied in sensing micro-and nano-scale strain. The experiments showed that the tunnel magnetoresistance MMS has an ability to measure both compressive and tensile stresses.…”
Section: Introductionmentioning
confidence: 99%